PERBANDINGAN KAPAL MONOHULL, CATAMARAN, TRIMARAN BERDASARKAN TINJAUAN OPERASIONAL PENGGUNAAN BAHAN BAKAR - Jacobus Tupan; Richard Benny Luhulima (Fakultas Teknik Universitas Pattimura, 2021)
In general, fishing fleets operating in Maluku waters and managed by local entrepreneurs consist of monohull and trimaran fishing vessels with outriggers. Monohull fishing vessels have limited deck space and poor transverse stability, while trimaran-type vessels have better deck space and transverse stability than monohull vessels, but because they are still in the form of outriggers, the space is limited. This study aims to examine the development of the trimaran fishing vessel in terms of energy requirements, safety, and comfort of the crew during fishing operations. The initial stage of this research begins with data analysis and the basic size of monohull fishing vessels operating in Maluku waters, from this data the shape of the trimaran hull is designed. Calculation of resistance using CFD, then analyzed the calculation of resistance and stability, safety, and comfort of the ship using Maxsurf. The drag Trimaran is 8.86% smaller than a monohull and 3.25% smaller than a catamaran. Energy Usage (EHP) is proven by trimaran ships more than other ship modes. The average trimaran period is 10.5 seconds which meets IMO standards and is declared operationally good.